Issues related to internet diffusion: a case study on ICT related projects in Sri Lanka - Madhubhashini, Galagedarage Thushari; Ali Salman,; Wan Amizah Wan Mahmood,; Fauziah Ahmad, (Universiti Kebangsaan Malaysian, 2013)
Internet user percentage in Sri Lanka has lingered at a mere 13.1% in 2011 according to an Annual report by Department of Census and Statistics in Sri Lanka. The aim of this paper is to identify the issues and problems of internet diffusion among rural communities in Sri Lanka. This conceptual paper is based on literature review. Reasons for Sri Lanka to experience a very low internet usage, due to social, economic, political, cultural and moral circumstances: no clear policy framework for facilitating the use of the Internet, lack of knowledge about the benefits of the new information technology, lack of motivation to use the Internet, economic problems, English Language barriers, attitudinal problems and inadequate infrastructure. ‘E- Sri Lanka’, ‘Horizon Lanka project’, ‘Virtual Village project’, ‘Kotmale Community Radio Internet project’ are ICT related projects in Sri Lanka. These ICT related programs are based in specific rural areas and there are experimental programs still trying to establish in other rural areas. There should be powerful and effective programs to empower rural and semi urban communities with ICT and English language literacy, skills and attitudinal motivation to access internet for socioeconomic development purposes.